2005
DOI: 10.1097/01.gim.0000160076.14102.ec
|View full text |Cite
|
Sign up to set email alerts
|

Detection and calibration of microdeletions and microduplications by array-based comparative genomic hybridization and its applicability to clinical genetic testing

Abstract: Purpose: Genome-wide telomere screening by fluorescence in situ hybridization (FISH) has revealed that Ϸ 6% of unexplained mental retardation is due to submicroscopic telomere imbalances. However, the use of FISH for telomere screening is labor intensive and time consuming, given that 41 telomeres are interrogated. We have evaluated the use of array-based Comparative Genomic Hybridization (aCGH) as a more efficient tool for identifying telomere rearrangements. Methods: In this study, 102 individuals with unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0
1

Year Published

2006
2006
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
5
27
0
1
Order By: Relevance
“…11 These clones were used in pilot FISH studies to interrogate imbalances involving 1p, 6q, 10q, 16p, 17p, and 22q. 8,[11][12][13] Although these pilot studies only included a small number of cases per telomere, they demonstrated the utility of this high-density mapping for more accurate clinical interpretation of telomere imbalances. By determining the size of each telomere imbalance, pathogenic imbalances could be differentiated from those that were apparently benign variants, such as small deletions and duplications of 4q and 10q.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 These clones were used in pilot FISH studies to interrogate imbalances involving 1p, 6q, 10q, 16p, 17p, and 22q. 8,[11][12][13] Although these pilot studies only included a small number of cases per telomere, they demonstrated the utility of this high-density mapping for more accurate clinical interpretation of telomere imbalances. By determining the size of each telomere imbalance, pathogenic imbalances could be differentiated from those that were apparently benign variants, such as small deletions and duplications of 4q and 10q.…”
mentioning
confidence: 99%
“…By determining the size of each telomere imbalance, pathogenic imbalances could be differentiated from those that were apparently benign variants, such as small deletions and duplications of 4q and 10q. 8,11 In this study, we have extended the use of FISH with our molecular ruler clone set to characterize a larger set of unbalanced telomere rearrangements. However, these analyses, as well as those of other investigators, 14,15 quickly led to the realization that many submicroscopic telomere imbalances were larger than 5 Mb and that additional bioinformatics and clone validation work to identify sequential clones for FISH mapping was inefficient and time-consuming.…”
mentioning
confidence: 99%
“…In general, these arrays contain clones targeting genomic regions of known clinical significance, for example, all known microdeletion syndrome regions and all subtelomeric regions, which are known to be frequently affected in patients with mental retardation. [21][22][23] As a consequence, these arrays are very well suited for screening these specific regions but only these regions. Still, this is an important clinical application with considerable diagnostic yield in patients submitted for a variety of developmental problems, as was demonstrated by the recent publication of Shaffer et al 24 The diagnostic yield of targeted as well as genomewide microarray analysis, however, strongly depends on the clinical selection as well as the previously performed cytogenetic analyses, and this may vary considerably between countries and even between institutions within countries.…”
Section: The Added Value Of Whole-genome Microarrays Over Targeted MImentioning
confidence: 99%
“…The FISH studies using specific telomeric probes/clones have suggested that these probes are suitable diagnostic tool at examination of the mental retardation, infertility, congenital anomalies, at investigation of rearrangements in the haematological malign tumours, and in the pre-implanting diagnoses as well as in other fields of clinical interest Bacino et al 2000;Knight & Flint 2000;Caliskan et al 2005). The submicroscopic telomeric deletions, that are not well visible after FISH, could be, according to Wong et al (2005), detected more precisely by means of an array-based comparative genomic hybridization (CGH).…”
Section: Satellite Probesmentioning
confidence: 99%